Utility of Ischemic Signs from Initial ECG in Detecting Culprit Vessels in NSTE-ACS Patients - Wijaya, Michael Asby; Haykal Putra, Teuku Muhammad; Widodo, Wishnu Aditya (Jurnal Kardiologi Indonesia, 2023)
Background: Non-ST-Elevation ACS (NSTE-ACS) is a part of ACS which require some special attentions. Multivessel coronary disease (MVD) is common in patients with NSTE-ACS and associated with difficulties in determining the main target of revascularization. ECG is the first-line diagnostic tool in the assessment of patients with suspected ACS. However, the utility of the ECG in localizing coronary culprit lesions in NSTE-ACS is not well established. This study was conducted to evaluate whether the pattern of the ischemic signs in ECG can be used to identify the coronary culprit vessel in patients with NSTE-ACS. Methods: This is a single-centered cross-sectional study using secondary data. The data of all 101 patients with NSTE-ACS who were planned for revascularization procedure between January 2021 and December 2021 were collected from medical record. ECG with ischemic signs were classified to three locations of suspected coronary vessel with culprit lesions and it will be compared to its corresponding angiographic data. The accuracy data will be presented including both sensitivity and specificity. Results: This study involved 75 men (74.3%) and 26 women (25.7%) with mean age 61.2±9.1 years old. There were 72 patients presented with ischemic signs form ECG with identifiable culprit vessel to be suspected. The sensitivity and specificity of ischemic signs ECG in localizing culprit vessels from angiography were 37.0% and 85.5% in LAD distribution, 38.1% and 81.3% in LCX distribution, and 41.1% and 85.1% in RCA distribution, respectively. Conclusion: Overall ischemic signs in ECG gave impression of modest accuracy with conspicuous key points that ECG distribution have high specificity in detecting culprit vessels but with low sensitivity. Thus, ischemic signs from initial ECG can be used to detect culprit vessels in NSTE-ACS patients.This article has a related Erratum.